2019
DOI: 10.1039/c9ra05867b
|View full text |Cite
|
Sign up to set email alerts
|

An erythrocyte membrane coated mimetic nano-platform for chemo-phototherapy and multimodal imaging

Abstract: The tumor variability and low efficiency associated with conventional chemical drugs provide an impetus to develop drug-carrying systems with targeted accumulation and controllable release behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…WBC membranes were shown to act as camouflaged surfaces that help to evade opsonization and RES clearance, as well as inflamed site-targeting navigators. This characteristic may (Xiao et al, 2019) endow WBC membrane-coated NPs with the ability to target some tumors (Fang et al, 2018). Thus, numerous WBC membrane-coated NPs have been developed for cancer chemotherapy, including monocyte cell membrane-coated PLGA NPs (Krishnamurthy et al, 2016), macrophage membrane-coated NPs (Zhang et al, 2018), platelet membrane (PM)-coated core-shell nanovehicles (Hu et al, 2015), and composite CM (derived from leukocytes and tumor cells)camouflaged liposomal NPs (He et al, 2018).…”
Section: Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…WBC membranes were shown to act as camouflaged surfaces that help to evade opsonization and RES clearance, as well as inflamed site-targeting navigators. This characteristic may (Xiao et al, 2019) endow WBC membrane-coated NPs with the ability to target some tumors (Fang et al, 2018). Thus, numerous WBC membrane-coated NPs have been developed for cancer chemotherapy, including monocyte cell membrane-coated PLGA NPs (Krishnamurthy et al, 2016), macrophage membrane-coated NPs (Zhang et al, 2018), platelet membrane (PM)-coated core-shell nanovehicles (Hu et al, 2015), and composite CM (derived from leukocytes and tumor cells)camouflaged liposomal NPs (He et al, 2018).…”
Section: Chemotherapymentioning
confidence: 99%
“…Benefiting from fluorescencephotoacoustic dual imaging and PTT, ICNPs could achieve realtime tumor monitoring with high spatial resolution and effective tumor treatment (Chen et al, 2016b). In addition to ICG, PB (Xiao et al, 2019), and Ce6 (Li et al, 2018a) were tested in combination with other agents using CM-based nanoplatforms in order to support a theranostic strategy. For instance, Xiao et al developed RBM-coated, DOX-loaded PB NPs that were modified with FA.…”
Section: In-vivo Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] These carriers include cells and their fragments, providing biocompatibility and natural mechanisms for transport, localization, and responsivity regarding microenvironments in the body. 6 Due to their high biocompatibility, red blood cells (RBC) [7][8][9][10][11][12] have potential as delivery systems in therapeutic applications. Indeed, therapeutic agents have already been loaded into carrier RBCs by, for example, electroporation, osmosis, bio-bridge methods, and cell-penetrating peptide methods.…”
Section: Introductionmentioning
confidence: 99%
“…13 A key role for carrier purposes is played by the dense glycan coating present in RBC membrane, 3 which provides immune evasion and stability in the blood circulation. 12,14,15 Aer a RBC has served its purpose, it is removed from the circulation by macrophages in spleen, liver, or lymph node, hence representing potential targets for designed RBC-based therapies. 13 Several studies have shown that engineered RBCs may have use in treating autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%